We are the song - Bakewell, Catherine (New York : Holiday House, 2022)
In Cadenza music is power, and twelve-year-old Elissa is one of twelve singers, voices of the Goddess, who can sing miracles into being and bring healing and hope to the world--but in the war torn kingdoms of the world there are rulers who would like to use her and her song to gain power instead, and Elissa stuggles to understand what the Goddess wants her to do, and how to protect herself, her composer, Lucio, and Cadenza itself.
Ages 8-12.
Grades 4-6.
Keywords: Singers -- Juvenile fiction; Songs -- Juvenile fiction; Magic -- Juvenile fiction; Composers -- Juvenile fiction; Goddesses -- Juvenile fiction; Singers -- Fiction; Songs -- Fiction; Magic -- Fiction; Composers -- Fiction; Goddesses -- Fiction; Fantasy